2021
DOI: 10.3390/cells10092452
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Synuclein and Lipids: The Elephant in the Room?

Abstract: Since the initial identification of alpha-synuclein (α-syn) at the synapse, numerous studies demonstrated that α-syn is a key player in the etiology of Parkinson’s disease (PD) and other synucleinopathies. Recent advances underline interactions between α-syn and lipids that also participate in α-syn misfolding and aggregation. In addition, increasing evidence demonstrates that α-syn plays a major role in different steps of synaptic exocytosis. Thus, we reviewed literature showing (1) the interplay among α-syn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 230 publications
(294 reference statements)
0
12
0
Order By: Relevance
“…23 Growing studies had shown that the accumulation of α-SYN in the SN accelerated the apoptosis of dopaminergic neurons and eventually led to PD. 24 We found that the intervention with L. plantarum DP189 reduced the accumulation of α-SYN, which also revealed that L. plantarum DP189 could resist the development of PD. Of note, the accumulation of α-SYN seems to be positively correlated with the oxidation level of the body.…”
Section: ■ Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…23 Growing studies had shown that the accumulation of α-SYN in the SN accelerated the apoptosis of dopaminergic neurons and eventually led to PD. 24 We found that the intervention with L. plantarum DP189 reduced the accumulation of α-SYN, which also revealed that L. plantarum DP189 could resist the development of PD. Of note, the accumulation of α-SYN seems to be positively correlated with the oxidation level of the body.…”
Section: ■ Discussionmentioning
confidence: 58%
“…As a key protein in the development of PD, α-SYN plays an important role in the production of PD . Growing studies had shown that the accumulation of α-SYN in the SN accelerated the apoptosis of dopaminergic neurons and eventually led to PD . We found that the intervention with L.…”
Section: Discussionmentioning
confidence: 73%
“…Because of the high curvature and increased phospholipid packing defects, αS preferentially binds to SUVs (∼40 nm diameter). These are comparable in size to vesicles found at the synaptic terminal of dopaminergic neurons, relative to large unilamellar vesicles (>100 nm) ( 41 , 42 , 43 ). Moreover, αS binding to lipid vesicles can act as an anchor point for aggregation, accelerating primary nucleation, and this is particularly the case at lower lipid:protein ratios because of the sufficiently high concentration of monomeric αS remaining in solution to contribute to fibril growth ( 27 , 32 , 38 ).…”
mentioning
confidence: 64%
“…Although the etiology of PD is generally unknown, the formation of α-syn aggregates seems to be closely associated to an altered lipid metabolism. Indeed, despite the fact that the physiological role of α-syn is yet not fully understood, it appears that its accumulation and aggregation are either enhanced by membrane lipid composition or they further cause alterations in lipid homeostasis [ 88 ]. Furthermore, genome-wide screening studies in yeast support the involvement of lipid metabolism in α-syn toxicity, with many genes associated with lipid metabolism, modifying toxicity, and vesicle-mediated transport [ 89 ].…”
Section: Lipids and Parkinson’s Diseasementioning
confidence: 99%